Une femme - Ernaux, Annie (Collection Folio, 1987)
Annie Ernaux s'efforce ici de retrouver les différents visages et la vie de sa mère, morte le 7 avril 1986, au terme d'une maladie qui avait détruit sa mémoire et son intégrité intellectuelle et physique. Elle, si active, si ouverte au monde. Quête de l'existence d'une femme, ouvrière, puis commerçante anxieuse de «tenir son rang» et d'apprendre. Mise au jour, aussi, de l'évolution et de l'ambivalence des sentiments d'une fille pour sa mère : amour, haine, tendresse, culpabilité, et, pour finir, attachement viscéral à la vieille femme diminuée. «Je n'entendrai plus sa voix... J'ai perdu le dernier lien avec le monde dont je suis issue.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; approches et analyses; care; classisme; cours; discipline; europe; famille; france; inégalités; lit301N; littérature; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques